(untitled) (Scientific journal of the Fergana State University, 2023)
The given article touches upon the issues of usage of indirect speech in different cultures. In the analyses of the indirect speech the analytical and descriptive methods were used. As the object of pragmalinguistics, the indirect speech involves the implicitness and its understanding by the addressee. The special attention is given to the implicitness in gender speech and its distinguishing features.